STUDENTS' READING INTERESTS SEEN FROM 4 LIBRARY MANAGEMENT FUNCTIONS - Sultan Isnani (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
This research aims to describe the implementation of library management in increasing students' reading interest at MTs. Dasrussal Anrong Appakah. This research uses a qualitative approach with a descriptive approach. Research location at MTs. Darussalam Anrong Appaka, The data sources in this research are primary data through the head of the madrassa tsanawiyah, head of library, teachers, students, and secondary data, namely data in studies or madrasa documents. The techniques used in collecting data are observation, interview and documentation techniques. Research results: The implementation of MTs Darussalam Anrong Appaka library management, apart from being seen from the planning aspect, can also be seen from the organizing, mobilizing and supervising aspects. From a planning aspect, the MTs library. Darussalam has planned activities in organizing the library including visit schedules, budgets, book procurement, human resources. From the organizational aspect, the MTs library. Darussalam has created an organizational structure, so that it can facilitate the library's performance according to its work, for example staffing, service and book classification, from the movement aspect, movement in the MTs library management aspect. Darussalam Anrong Appaka includes services and provision of advice and infrastructure. From the aspect of supervision, supervision in library management at MTs. Darussalam Anrong Appaka is intended to determine the effectiveness and efficiency of library management, in addition to obtaining quality improvements.